Influence of Financial Performance, Company Size and Company Age on Disclosure of Sustainability Reports in Non-Financial Companies on IDX 2019-2021 - Adhania, Lathanza; Nurdiana, Diah (PT. Riset Press International, 2024)
Most companies prioritize the interests of shareholders, while other parties do not receive special attention. In these conditions, many business world phenomena often ignore environmental and social problems. To support this problem, a concept is needed. This concept is called a sustainability report. The aims of this research is to analyze the influence of financial performances, firm size, and company age on the disclosure of non-financial companies' sustainability reports. This research uses a quantitative data in the form of secondary data: financial reports of companies obtained from the IDX. The sample was selected using purposive sampling method and the sample for this research includes 10 companies. This hypothesis testing uses multiple linear regression tests using SPSS version 26 software. The partial test results show that profitability has an influence on sustainability report disclosure, while firm size and company age do not influence sustainability report disclosure.